Misi Gereja Yang Visioner Dan Misioner Di Tengah Dunia Yang Berubah - Yakob Tomatala (Sekolah Tinggi Teologi Jaffray Jakarta, 2020)
The topic surrounding the visionary and missionary nature of the church is an ongoing discussion, which in turn could help churches in general to articulate the importance, responsibility, and role of the church. The entire dimension of being a Church have to be understood in order to give meaning for its presence on earth. When Jesus Christ said, “they (the Church) are being in the world, …..they (the Church) are being for the world (John 17:11b; 16b), He was referring to the complete substance of the Church. This reality underlies the fact that “the church have a heavenly body, but the church is also in the world therefore it has to be down to earth. Having a comprehensive understanding of this matter is important, to where this will enable the church to position itself accordingly in its respective context. With this knowledge and perspective, the Church can prove that it has “a visionary and missionary nature” to mark its presence as an instrument of God’s grace for the world with the right attitude and self positioning within the appropriate context with today’s condition.